Meta-analysis of risk factors for recurrence in cervical cancer patients following fertility-sparing treatment - Shi, Rui; Hou, Weili; Gao, Yanlei; Sun, Suli; Ling, Jia; Ma, Yaru (Frontiers in Surgery, 2026)
BackgroundTo identify and evaluate the main risk factors for recurrence in cervical cancer patients who undergo fertility- sparing treatment.MethodsA comprehensive search of multiple databases, including PubMed, Embase, and Web of Science, was performed to identify studies assessing the recurrence risk in cervical cancer patients treated with fertility-sparing procedures. Data from eligible studies were pooled, and the relative risks (RR) with 95% confidence intervals (CI) were calculated to evaluate the association between various risk factors and recurrence risk.ResultsTen studies met inclusion criteria. Recurrence risk was significantly higher in patients aged ≤30 years (RR: 2.03, 95% CI: 1.89–2.19), those with tumor size ≥2 cm (RR: 1.94, 95% CI: 1.82–2.06), stage > IA within the fertility-sparing spectrum (RR: 2.46, 95% CI: 2.29–2.64), lymphovascular space invasion (LVSI) positivity (RR: 2.09, 95% CI: 1.90–2.30), and lymph-node metastasis (RR 3.10, 95% CI 2.76–3.48). Heterogeneity was low across comparisons (I2≈0%), and no significant small-study effects were detected.ConclusionAge ≤30 years, tumor size ≥2 cm, stage > IA, LVSI positivity, and lymph-node metastasis are robust predictors of recurrence following fertility-sparing treatment in cervical cancer. Incorporating these variables into preoperative counseling, operative strategy, and follow-up planning may enhance oncologic safety while preserving reproductive potential in appropriately selected patients. Our findings are consistent with current guideline recommendations, which generally limit fertility-sparing approaches to tumors ≤2 cm, while tumors exceeding this threshold require cautious consideration and are usually not regarded as appropriate candidates outside of clinical trials or exceptional multidisciplinary contexts.